Research progress on the relationship between Helicobacter pylori infection and iron deficiency anemia - Pu, Sugui; Zhuang, Ze; Liu, Na; Luo, Qian; Zhang, Dekui (Frontiers in Microbiology, 2025)
Helicobacter pylori (H. pylori) infection affects around half of the global population and is a globally highly prevalent pathogen that is closely linked not only to gastrointestinal diseases such as chronic atrophic gastritis, functional dyspepsia and peptic ulcer but also to the development and progression of a variety of extra-gastrointestinal diseases. Numerous studies have shown the correlation between H. pylori infection and iron-deficiency anemia (IDA). The prevalence of H. pylori infection is higher in individuals with IDA, and the hemoglobin level of patients with IDA can be increased to different degrees or even returned to normal following active H. pylori eradication. However, this conclusion is still controversial. In this paper, a comprehensive literature search was conducted using the PubMed/MEDLINE/Web of Science database, combining the following terms: “Helicobacter pylori,” “Helicobacter pylori infection,” “iron deficiency anemia,” “iron deficiency,” “iron absorption,” “iron malabsorption,” “serum iron,” “hemoglobin,” “pathogenesis,” “mechanism,” and “eradication therapy.” Through extensive literature searches, the correlation between H. pylori infection and IDA, its potential mechanism, and the efficacy of H. pylori eradication therapy in IDA patients have been comprehensively discussed. We conclude that the majority of existing studies have confirmed the correlation between H. pylori infection and IDA, indicating that patients with H. pylori infection are more likely to develop IDA and that the prevalence of H. pylori infection is higher in individuals with IDA. Compared with iron supplementation alone, combining H. pylori eradication with iron supplementation is more effective in treating IDA, particularly in unexplained or refractory IDA cases. These findings provide valuable insights for clinicians managing patients with unexplained or refractory IDA.